2002
DOI: 10.17221/3504-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds of seed coats of white and coloured varieties of pea (Pisum sativum L.) and their total antioxidant activity

Abstract: The purpose of this study was to compare the composition and contents of phenolic acids and condensed tannin in the seed coats of white and coloured varieties of pea and to examine the antioxidant properties of methanol and acetone extracts containing these phenolic compounds. The contents of phenolic acids were quantified by the HPLC analysis. The sum of free phenolic acids, those liberated from soluble esters and those liberated from soluble glycosides, was higher for coloured seed coat (78.53 g per g dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 25 publications
6
72
0
3
Order By: Relevance
“…Xu and Chang [8] reported a lot of differences in the phenolic acid profile and flavan-3-ol composition of lentils, which are probably attributable to a number of factors, such as phenotype, crop location, and environmental stress. Other studies have reported changes in tannin content that depend on the color of the seed coat, as legumes with a dark seed coat have large amounts of phenolic compounds, especially for the anthocyanins and condensed tannin [45,46]. Also, Xu et al [44] determined a correlation between phenolic compounds and color value across five types of legume, whereby species with a colored seed coat have higher TPC, TFC and CTC, in comparison to species with paler colored seed coats; within species with colored seed coats (i.e., lentils and colored beans), there is a different phenolic composition in relation to the color variation.…”
Section: Antioxidant Compounds and Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Xu and Chang [8] reported a lot of differences in the phenolic acid profile and flavan-3-ol composition of lentils, which are probably attributable to a number of factors, such as phenotype, crop location, and environmental stress. Other studies have reported changes in tannin content that depend on the color of the seed coat, as legumes with a dark seed coat have large amounts of phenolic compounds, especially for the anthocyanins and condensed tannin [45,46]. Also, Xu et al [44] determined a correlation between phenolic compounds and color value across five types of legume, whereby species with a colored seed coat have higher TPC, TFC and CTC, in comparison to species with paler colored seed coats; within species with colored seed coats (i.e., lentils and colored beans), there is a different phenolic composition in relation to the color variation.…”
Section: Antioxidant Compounds and Antioxidant Activitymentioning
confidence: 99%
“…In addition, these compounds might be accumulated in plant tissues in response to cultivation in a marginal soil environment. The condensed tannins are located mainly in the testa, and they have an important role in the seed defense system, as they can act as antioxidants against oxidative damage caused by environmental factors [46]. Makoi and Ndakidemi [50] reported that the concentrations of flavonoids and anthocyanins are affected by the plant density and the cropping system.…”
Section: Antioxidant Compounds and Antioxidant Activitymentioning
confidence: 99%
“…The mean tannin content in black group was higher as compared to brown, green and yellow group of soybean genotypes. Tannins are biological active compounds widely found in lentil, pea, coloured soybean and other legumes (Takahata et al, 2001;Troszynska and Ciska 2002;Beninger and Hosfield 2003;Amarowicz et al, 2004). They are mainly located in testa and play an important role in the defense system of seeds that are exposed to oxidative damage by many environmental factors (Troszynska and Ciska, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Tannins are biological active compounds widely found in lentil, pea, coloured soybean and other legumes (Takahata et al, 2001;Troszynska and Ciska 2002;Beninger and Hosfield 2003;Amarowicz et al, 2004). They are mainly located in testa and play an important role in the defense system of seeds that are exposed to oxidative damage by many environmental factors (Troszynska and Ciska, 2002). Tannins and phenolic constituents bind with the proteins of saliva and the mucosal membrane of the mouth during mastication of food and adversely affect the utilization of proteins in animal and human diets (Akinyede et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The operation was repeated three-folds. After filtration and evaporation, the dry residue was weighed to calculate the yield of tannins [TROSZYNSTA and CISKA, 2002] .…”
Section: Quantitative Phytochemical Analysismentioning
confidence: 99%